2004
DOI: 10.1111/j.1600-051x.2004.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral rehabilitation with implant‐supported fixed partial dentures in periodontitis‐susceptible subjects

Abstract: The present randomized, controlled clinical trial that included partially edentulous periodontitis-susceptible subjects demonstrated that bone loss (i) during the first year of function as well as annually thereafter was small and (ii) did not vary between implants with machined- or rough-surface designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
208
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(237 citation statements)
references
References 24 publications
20
208
2
7
Order By: Relevance
“…At 6 weeks when the provisional prosthesis was placed, and at 6 months, 1-, 2-, 3-years after loading, standardized digital peri-apical radiographs were taken with paralleling technique using film holders ( cal analyses was not done in this study; however, it has already been done in one of their previous studies, 24 in which the mean difference between 2 readings was only 0.04 mm.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…At 6 weeks when the provisional prosthesis was placed, and at 6 months, 1-, 2-, 3-years after loading, standardized digital peri-apical radiographs were taken with paralleling technique using film holders ( cal analyses was not done in this study; however, it has already been done in one of their previous studies, 24 in which the mean difference between 2 readings was only 0.04 mm.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Some studies have found a positive correlation between smooth surface and peri-implant health (Astrand et al 2004;Esposito et al 2007), whereas others failed to find a correlation between type of implant surface and marginal bone loss (Gotfredsen and Karlsson 2001;Wennstrom et al 2004). Nevertheless, it is also shown that surface characteristics of the abutments may not influence biofilm formation, or the extent and cellular composition of the inflammatory lesion (Zitzmann et al 2002).…”
mentioning
confidence: 99%
“…Astrand et al 14 found that rough-surfaced implants had a higher incidence of peri-implantitis than smooth (turned) surfaces, whereas, Wennstrom et al 15 around implants that manifested peri-implantitis and those that were healthy, it was noted that the same types of bacteria were present around diseased and healthy implants; but an increased quantity of bacteria was found at diseased sites. Karoussis et al 24 reported that patients with a history of periodontitis manifested significantly greater probing depths, more peri-implant marginal bone loss, and a higher incidence of peri-implantitis.…”
Section: Jaypee Hs Grover Sagrika Shuklamentioning
confidence: 97%